Wandering spleen: a rare complication of sleeve gastrectomy. Issue 12 (5th December 2019) - Camarillo, Gerardo; Kopelman, Yael; Daskal, Yaakov; Sheffer, Daniel
Abstract : The spleen is an intraperitoneal organ typically located in the left upper quadrant. Ectopic ('wandering') spleen refers to the displacement of the spleen from its normal anatomical location to another region in the abdominal cavity or pelvis. It's a relatively rare condition with no clear aetiology. We present, here, a case of a wandering spleen following sleeve gastrectomy in a 23-year-old female patient, whose spleen, prior to this event, was demonstrated by imaging in a normal anatomical position. A splenectomy was performed, and after an uneventful postoperative period, the patient was discharged. No similar case description was found in the relevant medical literature. Possible causes and decision-making process are discussed. We conclude that the wandering spleen phenomenon should be considered in the differential diagnosis of patients presenting with abdominal pain and new abdominal mass following sleeve gastrectomy.